Advancement of optical methods and digital image correlation in experimental mechanics Proceedings of the 2020 Annual Conference on Experimental and Applied Mechanics - Lin, Ming-Tzer; Furlong, Cosme; Huang, Guozheng (Cham, Switzerland Springer, 2021)
Advancement of Optical Methods & Digital Image Correlation in Experimental Mechanics, Volume 4 of the Proceedings of the 2020 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the fourth volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on a wide range of optical methods ranging from traditional photoelasticity and interferometry to more recent DIC and DVC techniques, and includes papers in the following general technical research areas: DIC Methods & Its Applications Photoelsticity and Interferometry Applications Micro-Optics and Microscopic Systems Multiscale .
Electronic reproduction
Keywords: Optical measurements; Metrology; Materials -- Analysis; Photonics; Optical engineering; Optical materials; Mechanics, Applied; Electronic books